The Burden of Neurocysticercosis at a Single New York Hospital. (27th July 2020) - Spallone, Amy; Woroch, Luboslav; Sweeney, Keith; Seidman, Roberta; Marcos, Luis A.
Abstract : Neurocysticercosis (NCC), a disease caused by the larval pork tapeworm Taenia solium, has emerged as an important infection in the United States. In this study, we describe the spectrum of NCC infection in eastern Long Island, where there is a growing population of immigrants from endemic countries. A retrospective study was designed to identify patients diagnosed with NCC using ICD-9 and ICD-10 codes in the electronic medical records at Stony Brook University Hospital between 2005 and 2016. We identified 52 patients (56% male, median age: 35 years) diagnosed with NCC in the only tertiary medical center in Suffolk County. Twenty-five cases were reported in the last three years of the study. Forty-eight (94%) patients self-identified as Hispanic or Latino in the electronic medical record. Twenty-two (44%) and 28 (56%) patients had parenchymal and extraparenchymal lesions, respectively. Nineteen (41.3%) patients presented with seizures to the emergency department. Six patients (11.7%) had hydrocephalus, and five of them required frequent hospitalizations and neurosurgical interventions, including permanent ventriculoperitoneal shunts or temporary external ventricular drains. No deaths were reported. The minimum accumulated estimated cost of NCC hospitalizations during the study period for all patients was approximately 1.4 million United States dollars (USD). In conclusion, NCC predominantly affects young, Hispanic immigrants in Eastern Long Island, particularly in zip codes correlating to predominantly Hispanic communities. The number of cases diagnosed increased at an alarming rate during the study period. Our study suggests a growing need for screening high-risk patients and connecting patients to care in hopes of providing early intervention and treatment to avoid potentially detrimental neurological sequelae.